Implementation of the Pentahelix Stakeholders’ Role in Sustainable Tourism Development in Kenderan Tourism Village, Gianyar Regency - Bramanta, Khrisna; Putra Negarayana, Ida Bagus; Aridayanti, Dewa ayu (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2025)
This study aims to analyze the implementation of the Pentahelix model in the sustainable tourism development of Kenderan Tourism Village, Gianyar Regency, Bali. The Pentahelix model involves collaboration among five key stakeholders: government, academia, businesses, community, and media to foster inclusive and sustainable development. A qualitative descriptive method was employed, utilizing in-depth interviews, observation, and documentation for data collection. The findings reveal that all five elements of the Pentahelix have actively collaborated in supporting the sustainability of destination management, socio-economic empowerment, cultural preservation, and environmental conservation. The village government and tourism awareness group (Pokdarwis) served as the primary drivers, supported by academics and businesses in developing local products such as Sindrong oil. Local media contributed to tourism promotion and dissemination. While implementation has shown positive results, further enhancement in human resource capacity and indicator-based evaluation systems is needed. This research emphasizes the importance of cross-sector collaboration in realizing community-based sustainable tourism destinations.